2005
DOI: 10.1159/000083945
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Transforming Growth Factor-β<sub>2</sub> and Nitrated Chondroitin Sulfate Proteoglycans in Cerebrospinal Fluid Correlates with Poor Neurologic Outcome in Preterm Hydrocephalus

Abstract: Background: Progressive post-hemorrhagic hydrocephalus in preterm infants strongly predicts abnormal neurologic development, and often accompanies cystic periventricular leukomalacia (cPVL). Transforming growth factor-β1 (TGF-β1), associated with hydrocephalus, can upregulate the chondroitin sulfate proteoglycan (CSPG) synthesis. To date, CSPG and their nitrated metabolites (NT-CSPG) have not been evaluated in hydrocephalus. Objectives: We hypothesized that TGF-β1, TGF-β2<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 93 publications
0
10
1
Order By: Relevance
“…18,94 In support of this hypothesis, one study found a correlation between abnormal levels of TGF-β2 and extracellular matrix proteins (chondroitin sulfate proteoglycan) and the development of symptomatic PHH in preterm infants (in contrast to pre-term infants without PHH). 20 In an animal model of IVH, drugs that inhibit TGF-β2 were ineffective in controlling hydrocephalus. 2 In another human study of biomarkers specifcally implicated in impaired CSF absorption, the levels of TGF-β1 and aminoterminal propeptide of Type I collagen (PC1NP) were studied in neonates with symptomatic PHH, hydrocephalus from open spina bifida, and aqueductal stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…18,94 In support of this hypothesis, one study found a correlation between abnormal levels of TGF-β2 and extracellular matrix proteins (chondroitin sulfate proteoglycan) and the development of symptomatic PHH in preterm infants (in contrast to pre-term infants without PHH). 20 In an animal model of IVH, drugs that inhibit TGF-β2 were ineffective in controlling hydrocephalus. 2 In another human study of biomarkers specifcally implicated in impaired CSF absorption, the levels of TGF-β1 and aminoterminal propeptide of Type I collagen (PC1NP) were studied in neonates with symptomatic PHH, hydrocephalus from open spina bifida, and aqueductal stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, high protein levels in the CSF have been detected in hydrocephalus irrespective of radiologic obstruction to the CSF pathways. Higher levels of thrombopoietin [34], ferritin [35], nerve growth factor[36], chondroitin sulfate proteoglycan [37] transforming growth factor β1 [38,39], transforming growth factor β2 [37], S-100 protein [40,41], and vascular endothelial growth factor [42] have been found in ventricular CSF in patients with hydrocephalus resulting from intraventricular hemorrhage. Even in patients without any intraventricular blood, elevated proteins have been found in ventricular CSF in hydrocephalus resulting from intracranial schwannomas [7], a few cases of spinal schwannomas [8,9], and in about 4% of patients with Guillain-Barre' syndrome [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, high levels of proteins such as thrombopoietin (17), ferritin (18), nerve growth factor (19), chondroitin sulfate proteoglycan (20), transforming growth factor beta 1 (21,22), transforming growth factor beta 2 (20), S-100 protein (23,24), glial fibrillary acidic protein (GFAP) (24), neuron specific enolase (NSE) (24), myelin basic protein (MBP) (24), and vascular endothelial growth factor (25) within ventricular CSF, which may contribute to an elevation in osmolarity, have been observed in patients with hydrocephalus. Additionally, it has been shown that brain edema results from hyponatremia, which is evidence that there is free movement of water from the plasma into the brain tissue (26).…”
Section: Osmotic Gradient and Its Role In Hydrocephalusmentioning
confidence: 99%